Place Name Provinces in the Semitic-Speaking Ancient Near East - Isserlin, В. S. J.
A: Costal (= South-Western) Syria — East Canaanite Area — Genetic Relations between the Two Regions: Phonetic Distinctions, Consonants, Vowels, Position of Ugarit — Arabia — Sub-Regions: Western and Central-Eastern Arabia — Aramaic Area — West Semitic: Common Features — B: Evolution of West Semitic Topographic Nomenclature — C: East Semitic — Accadian and Westsemitic.